\[\boxed{\text{344\ (344).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ y = x^{2} - 12x + 3\]
\[a = 1 > 0 - \ \ ветви\ \]
\[направлены\ вверх.\]
\[x_{0} = \frac{12}{2} = 6;\]
\[y_{0} = 36 - 72 + 3 = - 33;\]
\[(6;\ - 33) - вершина\ параболы.\]
\[2)\ y = - x^{2} + 4x - 6\]
\[a = - 1 < 0 - \ \ ветви\ \]
\[направлены\ вниз.\]
\[x_{0} = \frac{- 4}{- 2} = 2;\]
\[y_{0} = - 4 + 8 - 6 = - 2;\]
\[(2;\ - 2) - вершина\ параболы.\]
\[3)\ y = 0,3x^{2} + 2,4x - 5\]
\[a = 0,3 > 0 - \ \ ветви\ \]
\[направлены\ вверх.\]
\[x_{0} = \frac{- 2,4}{0,6} = - 4;\]
\[y_{0} = 0,3 \cdot 16 - 2,4 \cdot 4 - 5 =\]
\[= - 9,8;\]
\[( - 4;\ - 9,8) - - вершина\ \]
\[параболы.\]
\[4)\ y = - 5x^{2} + 10x + 2\]
\[a = - 5 < 0 - \ \ ветви\ \]
\[направлены\ вниз.\]
\[x_{0} = \frac{- 10}{- 10} = 1;\]
\[y_{0} = - 5 + 10 + 2 = 7;\]
\[(1;7) - вершина\ параболы.\]
\[\boxed{\text{344.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ f(x) = \frac{x^{2} + 4x + 4}{x + 2}\]
\[x + 2 \neq 0\]
\[x \neq - 2.\]
\[D(f) = ( - \infty; - 2) \cup ( - 2; + \infty).\]
\[y = \frac{x^{2} + 4x + 4}{x + 2}\]
\[y = \frac{(x + 2)^{2}}{x + 2}\]
\[y = x + 2\]
\[x\] | \[0\] | \[1\] |
---|---|---|
\[y\] | \[2\] | \[3\] |
\[2)\ f(x) = \frac{x^{3}}{x};\ \ x \neq 0\]
\[D(f) = ( - \infty;0) \cup (0; + \infty).\]
\[y = \frac{x^{3}}{x}\]
\[y = x^{2}\]
\[x\] | \[1\] | \[2\] | \[- 1\] | \[- 2\] |
---|---|---|---|---|
\[y\] | \[1\] | \[4\] | \[1\] | \[4\] |
\(\ \)